Consensus on hearing aid candidature and fitting for mild hearing loss, with and without tinnitus: Delphi review - Sereda, Magdalena; Hoare, Derek J.; Nicholson, Richard; Smith, Sandra; Hall, Deborah A. (Lippincott, Williams & Wilkins, 2015)
Objectives: